Comparison Effect Of Vitamin C Vaginal Tablet Versus Oral Metronidazole For Treatment Of Bacterial Vaginosis - humadi, Esraa H. (Journal of the Faculty of Medicine Baghdad, 2011)
Back ground: Bcaterial vaginosis is an important gynecological problem, during reproductive age group with high relapse rate ,it is associated with high vaginal PH, vaginal vitamin C recently tried to decreased vaginal PH and treat bacterial vaginosis.Patients & Methods: One hundred and one women with Bacterial vaginosis their age range from 18-40 years enrolled in this study, the Diagnosis is confirmed by at least 3out of 4 of (Amsel criteria) which include a thin homogenous vaginal discharge, vaginal PH of ≥4.7, a characteristic ''amine odour'' release when alkali (lo% KOH) is added to a specimen of vaginal fluid, and at least 20% of epithelial cells having the appearance of clue cell in a wet mount of vaginal fluid or on gram stain . All women were randomly assigned to receive either 250mg vitamin C vaginal table at bed time for 6days (51patients) or oral metronidazole 500mg twice daily for 7days (50 patients) the patients were evaluated at two follow up visit 1st after treatment completed and 2nd one week later. Therapeutic success was defined as the presence of less than 3 Amsel criteria.Results: Regarding the infection with bacterial vaginosis no significant difference between two groups, (15.9%) of patients still infected with bacterial vaginosis at 1st follow up visit in (vagi-C) treated group. Compare to 26.7% of metronidazole group P=0.5, this confirmed at 2nd follow up visit P=0.1. Regarding vaginal PH there is significant reduction of vaginal PH in both groups at end of treatment P=0.0032 in Vagi-C, and P=0.0001 in metronidazole treated group.Conclusion: Vitamin C vaginal table 250mg has effective as oral metronidazole for treatment of bacterial vaginosis.